Teachers' practices in integrating education for sustainable development in the handicraft curriculum a multiple case study - Caragay, Kristyn Taduran (2012)
ABSTRACT This research used the multiple case study to determine the teachers' practices in integrating Education for Sustainable Development (ESD) in the Handicraft Curriculum of selected public secondary schools. The study was conducted in six localities in which were chosen using purposive and convenience sampling. The localities were Guimaras, Mt. Province, Banawe, Metro Manila, Albay, and Camarines Sur. Only one school in each locality was included in the study because of the limited number of schools offering handicraft classe (HCs). There were one to four teachers who handle the HC in each school. There were a total of ten handicraft teachers interviewed, utilizing a five-part questionnaire and an interview guide. The researcher also interviewed eight possible community partners (PCPs), using an interview guide. The results of the study showed that ESD is presently integrated in the HCs. The teachers perceived that Quality Education (QE), a requirement for ESD, existed at the level of the learner (i.e., there is learner-centered approach) but not at the level of the system (e.g., administrative support, budget allocation). On the part of the PCPs, all those interviewed were willing to hook up with the schools in the implementation of the Handicraft curriculum. Based on the identified needs of the teachers and gaps in the integration of ESD, the study recommends strengthened information dissemination and teacher development programs to enhance the integration of ESD in the Handicraft curriculum. The Handicraft curriculum itself needs to be revisited and reevaluated. Since school resources are limited, partnerships between schools, agencies, and communities should be forged.